2016
DOI: 10.18801/jstei.040116.29
|View full text |Cite
|
Sign up to set email alerts
|

Safe water access, motivation and community participation at arsenic affected rural area of Jessore, Bangladesh: insights and realism

Abstract: of arsenic affected people solved their arsenic problem by using arsenic safe water sources and its maintenance by user participation. Arsenic mitigation project activities were given a great benefit for awareness building and sustainable safe water supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The finding resonates with an earlier study that realised the need to balance access and quality issues in WASH service delivery, particularly in the developing world [ 27 ]. An earlier finding also confirmed females’ importance in dealing with contamination challenges and deep-rooted challenges such as arsenic [ 28 ]. In the context of Somalia, where the government and legislative system are weak, the water quality system is adversely affected.…”
Section: 0 Discussionmentioning
confidence: 58%
“…The finding resonates with an earlier study that realised the need to balance access and quality issues in WASH service delivery, particularly in the developing world [ 27 ]. An earlier finding also confirmed females’ importance in dealing with contamination challenges and deep-rooted challenges such as arsenic [ 28 ]. In the context of Somalia, where the government and legislative system are weak, the water quality system is adversely affected.…”
Section: 0 Discussionmentioning
confidence: 58%
“…A 100 ml sample was preserved by 2ml of 6N nitric acid for metal analysis but another 50ml sample was preserved in the refrigerator at 4˚C. The concentration of pH, TDS, total alkalinity, total hardness, sodium, potassium, calcium and magnesium were measured by membrane electrode, conductivity, Mohr's titration, acid-base titration, EDTA complex metric and flame-AAS method, respectively (Khan et al, 2016;Pandey and Bhatt, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Due to continuous drinking of this groundwater, inhabitants in that study area might suffer from several non-carcinogenic health hazards, including vomiting, abdominal pain, diarrhea, injury to the skin, gastrointestinal and respiratory tract infections, damage to the liver, cardiovascular, hematopoietic, and nervous system problems, diabetes, reproductive problems, hair loss, and neurological problems. Khan et al (2016) found that about 1,537 arsenicosis patients were assumed in Jashore district, while 375 arsenicosis patients were detected in Jhikargachha Upazila.…”
Section: Chronic Riskmentioning
confidence: 99%
“…According to the study results, about 97 and 73% of groundwater samples exceeded the WHO (0.01 mg/L) and Bangladesh Drinking Water Standard (BDWS) (0.05 mg/L) limits, respectively, whereas the mean concentration of As was 9 and 1.8 times higher than the WHO (0.01 mg/L) and BDWS (0.05 mg/L) limits. In the Jashore district, about 53% of surveyed tube-well water contains more than 50 μg/L of arsenic (Khan et al 2016). The concentrations of Fe in groundwater samples varied from 0.30 to 7.81 mg/L, with an average concentration of 3.68 + 1.72 mg/L (Table 1).…”
Section: Concentration Of Physicochemical Parameters In Groundwatermentioning
confidence: 99%
See 1 more Smart Citation